Phytochemical Analysis, Antioxidant and Antibacterial Activities of Some Medicinal Plants Growing in Nepal - Baskota, Manish; Pokhrel, Ananda; Khatri, Janak; Rimal, Prakash; Rajbhandari, Meena (Journal of Nepal Chemical Society, 2025)
Plants used in traditional medicines are the best options for the discovery, development, and delivery of new drugs. Hence the present study was conducted to evaluate the antioxidant and antibacterial activities, chemical screening, and estimation of phenolics, flavonoids, tannins, and sugars in different extracts of Ampelocissus daivaricata, Brassaiopsis hainla, Eranthemum pulchellum and Ficus cunia. These plants are commonly used in Nepalese traditional medicine to treat various diseases. In screening tests, phenolics, flavonoids, tannins glycosides, and reducing sugars were present in polar extracts. The higher amounts of phenolics (236.95±2.42 mg GAE/g extract), flavonoids (181.03±2.26 mg CE/g extract), and tannins (195.75±1.82 mg TAE/g extract) were present in the ethyl acetate extract of F. cunia. The higher amounts of sugars were present in the methanol extract (324.56 ± 0.299 mg GE/g extract) of A. daivaricata. In DPPH free radical scavenging assay, the ethyl acetate (24.64 ± 2.23 µg/mL) and methanol extract of F. cunia (24.71 ±1.67 µg/mL) showed similar IC50 values followed by the methanol extract of A. daivaricata (IC50:25.99 ± 0.94µg/mL) and ethyl acetate extract of B. hainla (IC50: 29.26±1.07 µg/mL). The extracts having higher amounts of phenolics and flavonoids showed greater antioxidant activities. In the antimicrobial assay, all the extracts showed a weak and narrow spectrum of activities.Some of the extracts of A. daivaricata, B. hainla, and F. Cunia showed activity against gram-positive bacteria. Only a few extracts were active against gram-negative bacteria. The extracts of B. hainla and F. cunia showed activity against C. albicans. The findings of this study support to some extent, the traditional use of these plants to treat microbial infections. These plants could be the source of new drugs to manage oxidative stress.